(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Communicative skills are fundamental to effective language education, enabling learners to express ideas, negotiate meaning, and engage in authentic social interaction. This paper examines the significance of communicative competence in language teaching through a comprehensive review of theoretical models, classroom practices, and empirical research. Data were collected via extensive literature reviews, classroom observations in diverse educational settings, and in-depth interviews with experienced language teachers. The study highlights that the integration of communicative activities—such as role-plays, task-based projects, and digital interactive platforms—enhances students’ linguistic proficiency, cultural awareness, and overall confidence. Challenges related to assessment methods, teacher preparedness, and curriculum constraints are discussed, and practical recommendations for educators and suggestions for future research are provided.